EFOMP's protocol quality controls in PET/CT and PET/MR. (January 2023) - Matheoud, Roberta; Boellaard, Ronald; Pike, Lucy; Ptacek, Jaroslav; Reynés-Llompart, Gabriel; Soret, Marine; Vandenberghe, Stefaan; Zorz, Alessandra; Julyan, Peter; Rausch, Ivo; Sattler, Bernhard; Manuel, Sanchez-Garcia; et al.
Highlights: EFOMP QC PET/CT and PET/MRI protocol document. QC tests to guarantee image quality, quantification accuracy and adequate radiation dose. Consists of easy-to-integrate practical tests for use in clinical practice. Allows users to detect changes in PET/CT/MRI system performance. Crucial for avoiding the short- and long-term system and image quality deterioration. Abstract: This article presents the protocol on Quality Controls in PET/CT and PET/MRI published online in May 2022 by the European Federation of Organisations for Medical Physics (EFOMP), which was developed by the Working group for PET/CT and PET/MRI Quality Control (QC) protocol. The main objective of this protocol was to comprehensively provide simple and practical procedures that may be integrated into clinical practice to identify changes in the PET/CT/MRI system's performance and avoid short- and long-term quality deterioration. The protocol describes the quality control procedures on radionuclide calibrators, weighing scales, PET, CT and MRI systems using selected and measurable parameters that are directly linked to clinical images quality. It helps to detect problems before they can impact clinical studies in terms of safety, image quality, quantification accuracy and patient radiation dose. CT and MRI QCs are described only in the context of their use for PET (attenuation correction and anatomical localization) imaging. Detailed step-by-step instructions have been provided, limiting any misinterpretations or interpersonal variations as much as possible. This paper presents the main characteristics of the protocol illustrated together with a brief summary of the content of each chapter. A regular QC based on the proposed protocol would guarantee that PET/CT and PET/MRI systems operate under optimal conditions, resulting in the best performance for routine clinical tasks.